The Relation of T-Shirt Product Digital Marketing Model, Social Media Use, And Consumer Background - Rodhiah Rodhiah; Nur Hidayah (Sultan Publisher, 2025)
Due to its adherence to international trends, fashion is developing at a quick pace these days. One of them is the t-shirt, which, to stay up with technological changes, is now sold through digital media like online stores. To maximize earnings, it is crucial to establish a digital marketing strategy that suits customer preferences. Thus, this study seeks to ascertain that consumer background positively influences social media usage by customers and that social media usage positively influences the digital marketing model of t-shirt items. The population of students attending private universities in West Jakarta is the focus of this study. Purposive sampling is the method used to select the sample for the study. A Google Form questionnaire was used to collect data, and 100 respondents were chosen as the sample size. SEM analysis using Smart PLS was the data analysis method employed. The findings of the study demonstrate that managerial skill significantly and favourably affects financial performance. Financial performance is positively and significantly impacted by operational capability. Although it is not statistically significant, sustainability strategy favourably moderates the association between managerial skill and financial performance. The relationship between financial performance and operational capabilities is strongly and negatively moderated by sustainability strategy.